2017
DOI: 10.5312/wjo.v8.i4.342
|View full text |Cite
|
Sign up to set email alerts
|

RANK-ligand and osteoprotegerin as biomarkers in the differentiation between periprosthetic joint infection and aseptic prosthesis loosening

Abstract: AIMTo assess serum levels of RANK-ligand (RANKL) and osteoprotegerin (OPG) as biomarkers for periprosthetic joint infection (PJI) and compare their accuracy with standard tests.METHODSOne hundred and twenty patients presenting with a painful total knee or hip arthroplasty with indication for surgical revision were included in this prospective clinical trial. Based on standard diagnostics (joint aspirate, microbiological, and histological samples) and Musculoskeletal Infection Society consensus classification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A moderate upregulation of RANKL at the osteolytic cite compared to a distant site was also reported (31). In addition, there was no deference in the serum level of RANKL in patients with PJI and aseptic loosening (32).…”
Section: Osteolysismentioning
confidence: 73%
“…A moderate upregulation of RANKL at the osteolytic cite compared to a distant site was also reported (31). In addition, there was no deference in the serum level of RANKL in patients with PJI and aseptic loosening (32).…”
Section: Osteolysismentioning
confidence: 73%
“…Studies have revealed that OPG plays an important role in inhibiting osteoclastogenesis as a final effector of bone formation. 31 In this study, OPG was released from the double-layered nanoparticles in group A, which inhibited the differentiation and maturation of osteoclasts. Compared with group B, only a small amount of OPG was released from the nanoparticles, so the inhibitory effect on the generation of osteoclasts was not as strong as that in group B.…”
Section: In Vitro Biological Activity Of the Double-layered Nanopartimentioning
confidence: 68%
“…Despite improvements in prosthetic design and surgical techniques, aseptic loosening resulting from osteolysis or peri-prosthetic bone loss is a major cause of premature failure of prosthetic knee surgery. The diagnosis of early aseptic loosening is based on clinical and radiographic evaluation, but biomarkers are currently gaining interest for the preoperative differentiation between septic and aseptic loosening (1).…”
Section: Introductionmentioning
confidence: 99%
“…Collecting these data could help to estimate the risk of aseptic loosening even before implantation of the first prosthesis (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%